Radiation-induced skin injury: a review of pathophysiology, assessment, management, and re-irradiation protocols - Cheng, Jiao; Dong, Juancong; Fang, Yuan; Zhang, Xiaoquan; Dang, Xuhong (Frontiers in Oncology, 2026)
BackgroundRadiation-induced skin injury (RISI) is a common dose-limiting toxicity of radiotherapy, characterized by erythema, desquamation, fibrosis, atrophy, and ulceration. It results from DNA damage, reactive oxygen species, and dysregulated inflammation.PurposeThis review synthesizes current knowledge on the mechanisms, assessment tools, and management strategies of RISI, with a focus on emerging therapeutic approaches, particularly in patients requiring re-irradiation.Materials and methodsA search of PubMed, Embase, and Web of Science for English-language studies from 2020 to 2025 using terms like “radiation dermatitis,” “skin toxicity,” and “stem cell therapy” identified 122 pre-clinical and clinical studies.ResultsKey grading tools for RISI include the Radiation Therapy Oncology Group (RTOG), Common Terminology Criteria for Adverse Events (CTCAE), and Radiation-Induced Skin Reaction Assessment Scale (RISRAS). Conventional treatments like corticosteroids and emollients alleviate symptoms but do not prevent chronic damage. Novel therapies, including mesenchymal stem cells and mitochondrial-targeted antioxidants, show promise in reducing dermal injury and enhancing repair. Re-irradiated patients experience increased severe dermatitis, highlighting the need for better dose-to-skin constraints.ConclusionWhile current management remains mostly palliative, emerging therapies when guided by standardized assessment tools (including the widely used RTOG scale, which remains the clinical gold standard for skin toxicity grading), alongside CTCAE and RISRAS and individualized treatment planning offer hope for reducing acute and long-term skin damage, especially in re-irradiation cases.